The YopB protein of Yersinia pseudotuberculosis is essential for the translocation of Yop effector proteins across the target cell plasma membrane and displays a contact-dependent membrane disrupting activity. - Håkansson, S (1996)
During infection of cultured epithelial cells, surface-located Yersinia pseudotuberculosis deliver Yop (Yersinia outer protein) virulence factors into the cytoplasm of the target cell. A non-polar yopB mutant strain displays a wild-type phenotype with respect to in vitro Yop regulation and secretion but fails to elicit a cytotoxic response in cultured HeLa cells and is unable to inhibit phagocytosis by macrophage-like J774 cells. Additionally, the yopB mutant strain was avirulent in the mouse model. No YopE or YopH protein were observed within HeLa cells infected with the yopB mutant strain, suggesting that the loss of virulence of the mutant strain was due to its inability to translocate Yop effector proteins through the target cell plasma membrane. Expression of YopB is necessary for Yersinia-induced lysis of sheep erythrocytes. Purified YopB was shown to have membrane disruptive activity in vitro. YopB-dependent haemolytic activity required cell contact between the bacteria and the erythrocytes and could be inhibited by high, but not low, molecular weight carbohydrates. Similarly, expression of YopE reduced haemolytic activity. Therefore, we propose that YopB is essential for the formation of a pore in the target cell membrane that is required for the cell-to-cell transfer of Yop effector proteins.